2007
DOI: 10.3138/cmlr.64.1.039
|View full text |Cite
|
Sign up to set email alerts
|

Research on Integrated Performance Assessment at the Post-Secondary Level: Student Performance Across the Modes of Communication

Abstract: This article reports on a performance-based assessment research project conducted at the US Air Force Academy during the 2004–2005 academic year. The primary purpose of the research project was to measure post-secondary students’ progress towards meeting the Standards for Foreign Language Learning in the 21st Century – specifically the three modes of communication. The article explains how Integrated Performance Assessment measures learners’ language performance in light of current research in foreign language… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 22 publications
5
33
0
Order By: Relevance
“…The primary purpose of this study was to determine if using performance-based assessments had any effect on students' language learning process (Glisan et al, 2007). As a result, the article reported that PBAs improved students' oral skills and encouraged teachers to connect teaching, learning, and evaluation effectively.…”
Section: Theory and Practice In Language Studies 2443mentioning
confidence: 99%
See 4 more Smart Citations
“…The primary purpose of this study was to determine if using performance-based assessments had any effect on students' language learning process (Glisan et al, 2007). As a result, the article reported that PBAs improved students' oral skills and encouraged teachers to connect teaching, learning, and evaluation effectively.…”
Section: Theory and Practice In Language Studies 2443mentioning
confidence: 99%
“…When instructors implement authentic assessment in classrooms where English is taught as a foreign language (EFL), they give students the opportunity to demonstrate their active use of English to complete tasks or solve problems (Glisan et al, 2007;McKay, 2006). Therefore, they can motivate students to see English as a real means of communication.…”
Section: A Authentic Assessmentsmentioning
confidence: 99%
See 3 more Smart Citations